Balancing biofuel production and biodiversity: Harvesting frequency effects on production and community composition in planted tallgrass prairie. (September 2016) - Stahlheber, Karen A.; Watson, Bradley; Dickson, Timothy L.; Disney, Ryan; Gross, Katherine L.
Abstract: Native perennial grasslands have been proposed as a source of feedstocks for the production of second-generation lignocellulosic biofuels in the Midwestern USA. Although the consequences of some management decisions for biomass production and plant community composition are well understood (e.g. fertilization), less is known about the effects of harvesting frequency. We compared a once- and twice-annual harvesting regime at two restored prairies in southwestern Michigan established with identical seed mixtures as part of a large-scale bioenergy experiment. We determined biomass production and species composition in experimental plots and also measured the availability of light, inorganic nitrogen and soil moisture. The plant communities that established at the two sites differed markedly in composition and there was little evidence of convergence after five years. At the site dominated by warm-season C4 grasses, single harvests generally produced more biomass than double harvests. By contrast, biomass production was unaffected by harvesting at the more diverse site. Contrary to our prediction that a summer harvest would increase diversity, we found small and subtle effects on plant community composition. This may be due in part to the timing of our harvest treatment. Our results suggest that a single, end-of-season harvest is the best practice for maximizing biomass production in prairies, especially at sites where warm-season grasses dominate. However, at more diverse sites, two harvests can produce the same total biomass and may support other beneficial ecosystem services. This study indicates that in the short term, double harvests are unlikely to affect plant species diversity or community composition in prairie plantings. Highlights: Establishment and eventual plant community composition of tallgrass prairie planted for biofuel can vary considerably among locations. Responses to harvesting frequency depend on plant community. Sites dominated by warm-season grasses produced the most biomass with one harvest. Biomass production at sites with more diverse plant communities was similar with one or two annual harvests. Harvesting twice increased abundance of legumes, but not plant species richness or diversity.